An Anchor for the Region: Examining a Regional Comprehensive University's Efforts to Serve its Rural, Appalachian Community - Cecilia Orphan; Kevin McClure (Journal of Research in Rural Education, 2019)
Recent media reporting and research suggest that regional comprehensive universities (RCUs) and other postsecondary institutions may play an integral role in the welfare of rural regions, yet empirical research on the regional service of rural postsecondary institutions is limited. The purpose of this study was to examine how a single RCU serves its rural, Appalachian region. Guided by case study methods, this study used a theoretical framework consisting of community capitals theory and the anchor institution framework. After analysis of interview, documentary, governmental, and observational data, the case study resulted in a rich description of the RCU's regional service. Our findings demonstrate the RCU's role as an anchor institution as it expended resources to grow, invest in, and leverage rural community capitals. The university's most significant focus as an anchor institution was on leveraging and increasing human capital through investing in education, workforce development, and public health. These findings point to several implications and policy recommendations to better support the anchor institution role RCUs play in rural regions.